Magnetic Reconnection Inside a Flux Rope Induced by Kelvin‐Helmholtz Vortices. Issue 4 (8th April 2020) - Hwang, K.‐J.; Dokgo, K.; Choi, E.; Burch, J. L.; Sibeck, D. G.; Giles, B. L.; Hasegawa, H.; Fu, H. S.; Liu, Y.; Wang, Z.; Nakamura, T. K. M.; Ma, X.; et al.
Abstract: On 5 May 2017, MMS observed a crater‐type flux rope on the dawnside tailward magnetopause with fluctuations. The boundary‐normal analysis shows that the fluctuations can be attributed to nonlinear Kelvin‐Helmholtz (KH) waves. Reconnection signatures such as flow reversals and Joule dissipation were identified at the leading and trailing edges of the flux rope. In particular, strong northward electron jets observed at the trailing edge indicated midlatitude reconnection associated with the 3‐D structure of the KH vortex. The scale size of the flux rope, together with reconnection signatures, strongly supports the interpretation that the flux rope was generated locally by KH vortex‐induced reconnection. The center of the flux rope also displayed signatures of guide‐field reconnection (out‐of‐plane electron jets, parallel electron heating, and Joule dissipation). These signatures indicate that an interface between two interlinked flux tubes was undergoing interaction, causing a local magnetic depression, resulting in an M‐shaped crater flux rope, as supported by reconstruction. Plain Language Summary: Magnetic reconnection and Kelvin‐Helmholtz instability (KHI), two of the most fundamental physical processes occurring within the heliosphere and throughout the Universe, often occur simultaneously on the Earth's magnetopause. Previous studies indicate the importance of nonlinearly developed KH waves, which produce multiple kinetic layers facilitating reconnection both in and out of the velocity shear plane and resulting in the magnetic flux rope. However, these studies significantly lacked detailed in situ observations in quantity as well as appropriate 3‐D analyses of the structure of the KH vortex‐induced flux rope. In this paper, we use detailed observations by the MMS spacecraft to investigate both 2‐D and 3‐D structures of the flux rope developed along the KH waves. We found that two flux tubes interact through reconnection to form a single combined structure, which can explain the occurrence of M‐shaped crater flux rope. Key Points: MMS observed a magnetic flux rope formed on the boundary of a nonlinear Kelvin‐Helmholtz (KH) wave Both in‐plane and midlatitude reconnection associated with the 3‐D structure of the KH vortex‐inducedflux rope were identified A current sheet at the flux rope center supported by reconstruction indicates two flux tubes interlinked to form a crater‐type flux rope